The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

occTest : An integrated approach for quality control of species occurrence data - Josep M. Serra‐Diaz; Jeremy Borderieux; Brian Maitner; Coline C. F. Boonman; Daniel Park; Wen‐Yong Guo; Arnaud Callebaut; Brian J. Enquist; Jens‐C. Svenning; Cory Merow (Global Ecology and Biogeography, 2024)
Aim Species occurrence data are valuable information that enables one to estimate geographical distributions, characterize niches and their evolution, and guide spatial conservation planning. Rapid increases in species occurrence data stem from increasing digitization and aggregation efforts, and citizen science initiatives. However, persistent quality issues in occurrence data can impact the accuracy of scientific findings, underscoring the importance of filtering erroneous occurrence records in biodiversity analyses. Innovation We introduce an R package, occTest, that synthesizes a growing open‐source ecosystem of biodiversity cleaning workflows to prepare occurrence data for different modelling applications. It offers a structured set of algorithms to identify potential problems with species occurrence records by employing a hierarchical organization of multiple tests. The workflow has a hierarchical structure organized in test Phases (i.e. cleaning vs. testing) that encompass different testBlocks grouping different testTypes (e.g. environmental outlier detection ), which may use different testMethods (e.g. Rosner test, jacknife, etc.). Four different testBlocks characterize potential problems in geographic, environmental, human influence and temporal dimensions. Filtering and plotting functions are incorporated to facilitate the interpretation of tests. We provide examples with different data sources, with default and user‐defined parameters. Compared to other available tools and workflows, occTest offers a comprehensive suite of integrated tests, and allows multiple methods associated with each test to explore consensus among data cleaning methods. It uniquely incorporates both coordinate accuracy analysis and environmental analysis of occurrence records. Furthermore, it provides a hierarchical structure to incorporate future tests yet to be developed. Main conclusions occTest will help users understand the quality and quantity of data available before the start of data analysis, while also enabling users to filter data using either predefined rules or custom‐built rules. As a result, occTest can better assess each record's appropriateness for its intended application.

Temporal shifts in the functional composition of Andean forests at different elevations are driven by climate change - Johanna Andrea Martínez‐Villa; Sandra M. Durán; Brian J. Enquist; Alvaro Duque; Christian Messier; Alain Paquette (Global Ecology and Biogeography, 2024)
Aim Andean forests are a global biodiversity hotspot. They harbour many species living within narrow climate ranges and a high functional diversity of trees. It remains still unclear how such hotspots respond to climatic changes over time. We investigated whether Andean forests are changing their functional composition over time along an elevational gradient by assessing changes in species composition, abundance and functional traits. Location An elevational gradient in Colombia's northern Andes. Time Period Species composition changes were studied two to four times from 2006 to 2017, and functional composition from 2016 to 2017. Major Taxa Studied A total of 1104 tropical tree species with in situ traits characterization. Methods We used seven morphological leaf traits and wood density values to analyse the functional trait dynamic over 10 years along an elevational gradient. By analysing changes in species composition, abundance and trait representation, we inferred the magnitude and direction of changes in functional composition. Then, we assessed if the functional change was related to climate change and demography. Results With increased minimum temperature and vapour‐pressure deficit, we found a decrease over time in mean values for leaf area and specific leaf area and increases in leaf thickness and leaf dry matter content. Long‐term temperature increases are smaller with increasing elevation, but the magnitude of trait changes is greater than in lowlands. Main Conclusions The functional composition is changing towards more conservative strategies over time across the elevation gradient, with the strongest changes observed at the highest elevations. This pattern is explained by the change in species turnover within communities due to higher recruitment rates of species with high leaf dry matter content values and low leaf area values. These shifts may be related to communities' responses to higher evapotranspiration demand and thermal stress, mainly at higher elevations.

Global dominance of lianas over trees is driven by forest disturbance, climate and topography - Alain Senghor K. Ngute; David S. Schoeman; Marion Pfeifer; Geertje M. F. van der Heijden; Oliver L. Phillips; Michiel van Breugel; Mason J. Campbell; Chris J. Chandler; Brian J. Enquist; Rachael V. Gallagher; Christoph Gehring; Jefferson S. Hall; et al. (Global Change Biology, 2024)
Growing evidence suggests that liana competition with trees is threatening the global carbon sink by slowing the recovery of forests following disturbance. A recent theory based on local and regional evidence further proposes that the competitive success of lianas over trees is driven by interactions between forest disturbance and climate. We present the first global assessment of liana–tree relative performance in response to forest disturbance and climate drivers. Using an unprecedented dataset, we analysed 651 vegetation samples representing 26,538 lianas and 82,802 trees from 556 unique locations worldwide, derived from 83 publications. Results show that lianas perform better relative to trees (increasing liana‐to‐tree ratio) when forests are disturbed, under warmer temperatures and lower precipitation and towards the tropical lowlands. We also found that lianas can be a critical factor hindering forest recovery in disturbed forests experiencing liana‐favourable climates, as chronosequence data show that high competitive success of lianas over trees can persist for decades following disturbances, especially when the annual mean temperature exceeds 27.8°C, precipitation is less than 1614 mm and climatic water deficit is more than 829 mm. These findings reveal that degraded tropical forests with environmental conditions favouring lianas are disproportionately more vulnerable to liana dominance and thus can potentially stall succession, with important implications for the global carbon sink, and hence should be the highest priority to consider for restoration management.

The ecological causes of functional distinctiveness in communities - François Munoz; Christopher A. Klausmeier; Pierre Gaüzère; Gaurav Kandlikar; Elena Litchman; Nicolas Mouquet; Annette Ostling; Wilfried Thuiller; Adam C. Algar; Arnaud Auber; Marc W. Cadotte; Léo Delalandre; et al. (Ecology Letters, 2023)
Recent work has shown that evaluating functional trait distinctiveness, the average trait distance of a species to other species in a community offers promising insights into biodiversity dynamics and ecosystem functioning. However, the ecological mechanisms underlying the emergence and persistence of functionally distinct species are poorly understood. Here, we address the issue by considering a heterogeneous fitness landscape whereby functional dimensions encompass peaks representing trait combinations yielding positive population growth rates in a community. We identify four ecological cases contributing to the emergence and persistence of functionally distinct species. First, environmental heterogeneity or alternative phenotypic designs can drive positive population growth of functionally distinct species. Second, sink populations with negative population growth can deviate from local fitness peaks and be functionally distinct. Third, species found at the margin of the fitness landscape can persist but be functionally distinct. Fourth, biotic interactions (positive or negative) can dynamically alter the fitness landscape. We offer examples of these four cases and guidelines to distinguish between them. In addition to these deterministic processes, we explore how stochastic dispersal limitation can yield functional distinctiveness. Our framework offers a novel perspective on the relationship between fitness landscape heterogeneity and the functional composition of ecological assemblages.

How to improve scaling from traits to ecosystem processes - Julia Chacón-Labella; Cesar Hinojo-Hinojo; Teresa Bohner; Matiss Castorena; Cyrille Violle; Vigdis Vandvik; Brian J. Enquist (Trends in Ecology & Evolution, 2023)

A review of the heterogeneous landscape of biodiversity databases: Opportunities and challenges for a synthesized biodiversity knowledge base - Xiao Feng; Brian J. Enquist; Daniel S. Park; Brad Boyle; David D. Breshears; Rachael V. Gallagher; Aaron Lien; Erica A. Newman; Joseph R. Burger; Brian S. Maitner; Cory Merow; Yaoqi Li; et al. (Global Ecology and Biogeography, 2022)
Aim Addressing global environmental challenges requires access to biodiversity data across wide spatial, temporal and taxonomic scales. Availability of such data has increased exponentially recently with the proliferation of biodiversity databases. However, heterogeneous coverage, protocols, and standards have hampered integration among these databases. To stimulate the next stage of data integration, here we present a synthesis of major databases, and investigate (a) how the coverage of databases varies across taxonomy, space, and record type; (b) what degree of integration is present among databases; (c) how integration of databases can increase biodiversity knowledge; and (d) the barriers to database integration. Location Global. Time period Contemporary. Major taxa studied Plants and vertebrates. Methods We reviewed 12 established biodiversity databases that mainly focus on geographic distributions and functional traits at global scale. We synthesized information from these databases to assess the status of their integration and major knowledge gaps and barriers to full integration. We estimated how improved integration can increase the data coverage for terrestrial plants and vertebrates. Results Every database reviewed had a unique focus of data coverage. Exchanges of biodiversity information were common among databases, although not always clearly documented. Functional trait databases were more isolated than those pertaining to species distributions. Variation and potential incompatibility of taxonomic systems used by different databases posed a major barrier to data integration. We found that integration of distribution databases could lead to increased taxonomic coverage that corresponds to 23 years’ advancement in data accumulation, and improvement in taxonomic coverage could be as high as 22.4% for trait databases. Main conclusions Rapid increases in biodiversity knowledge can be achieved through the integration of databases, providing the data necessary to address critical environmental challenges. Full integration across databases will require tackling the major impediments to data integration: taxonomic incompatibility, lags in data exchange, barriers to effective data synchronization, and isolation of individual initiatives.

Plant community impact on productivity: Trait diversity or key(stone) species effects? - Philipp Brun; Cyrille Violle; David Mouillot; Nicolas Mouquet; Brian J. Enquist; François Munoz; Tamara Münkemüller; Annette Ostling; Niklaus E. Zimmermann; Wilfried Thuiller (Ecology Letters, 2022)
Outside controlled experimental plots, the impact of community attributes on primary productivity has rarely been compared to that of individual species. Here, we identified plant species of high importance for productivity (key species) in >29,000 diverse grassland communities in the European Alps, and compared their effects with those of community‐level measures of functional composition (weighted means, variances, skewness and kurtosis). After accounting for the environment, the five most important key species jointly explained more deviance of productivity than any measure of functional composition alone. Key species were generally tall with high specific leaf areas. By dividing the observations according to distinct habitats, the explanatory power of key species and functional composition increased and key‐species plant types and functional composition‐productivity relationships varied systematically, presumably because of changing interactions and trade‐offs between traits. Our results advocate for a careful consideration of species’ individual effects on ecosystem functioning in complement to community‐level measures.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Human food use increases plant geographical ranges in the Sonoran Desert - Carolyn Flower; Wendy C. Hodgson; Andrew M. Salywon; Brian S. Maitner; Brian J. Enquist; Matthew A. Peeples; Benjamin Blonder (Global Ecology and Biogeography, 2021)
Aim Climate is usually regarded as the main determinant of plant species distributions. However, past human use of species for food might also have influenced distributions. We hypothesized that human‐mediated dispersal has resulted in food plants occupying more of their potential geographical range. We also hypothesized that key ecological traits could predispose a species to occupy more of its potential climatic geographical range and be selected by humans for food. Location The Sonoran Desert of south‐western North America. Time period Present day. Major taxa studied Food plants. Methods We used ethnobotanical data and data from large botanical ecoinformatics databases to estimate realized (dispersal‐ and climate‐constrained) and potential (climate‐constrained) ranges for food plants and their used and unused congeners. Results We found that food plants fill more of their potential geographical ranges than their unused congeners. We also found that succulence and annual growth interacted with food usage to increase range filling. Main conclusions Human food use has expanded the distribution of many plant species in the Sonoran Desert.

Global gradients in intraspecific variation in vegetative and floral traits are partially associated with climate and species richness - Jonas Kuppler; Cécile H. Albert; Gregory M. Ames; William Scott Armbruster; Gerhard Boenisch; Florian C. Boucher; Diane R. Campbell; Liedson T. Carneiro; Eduardo Chacón‐Madrigal; Brian J. Enquist; Carlos R. Fonseca; José M. Gómez; et al. (Global Ecology and Biogeography, 2020)
Aim Intraspecific trait variation (ITV) within natural plant communities can be large, influencing local ecological processes and dynamics. Here, we shed light on how ITV in vegetative and floral traits responds to large‐scale abiotic and biotic gradients (i.e., climate and species richness). Specifically, we tested whether associations of ITV with temperature, precipitation and species richness were consistent with any of four hypotheses relating to stress tolerance and competition. Furthermore, we estimated the degree of correlation between ITV in vegetative and floral traits and how they vary along the gradients. Location Global. Time period 1975–2016. Major taxa studied Herbaceous and woody plants. Methods We compiled a dataset of 18,401 measurements of the absolute extent of ITV (measured as the coefficient of variation) in nine vegetative and seven floral traits from 2,822 herbaceous and woody species at 2,372 locations. Results Large‐scale associations between ITV and climate were trait specific and more prominent for vegetative traits, especially leaf morphology, than for floral traits. The ITV showed pronounced associations with climate, with lower ITV values in colder areas and higher values in drier areas. The associations of ITV with species richness were inconsistent across traits. Species‐specific associations across gradients were often idiosyncratic, and covariation in ITV was weaker between vegetative and floral traits than within the two trait groups. Main conclusions Our results show that, depending on the traits considered, ITV either increased or decreased with climate stress and species richness, suggesting that both factors can constrain or enhance ITV, which might foster plant‐population persistence in stressful conditions. Given the species‐specific responses and covariation in ITV, associations can be hard to predict for traits and species not yet studied. We conclude that consideration of ITV can improve our understanding of how plants cope with stressful conditions and environmental change across spatial and biological scales.

Leaf size of woody dicots predicts ecosystem primary productivity - Yaoqi Li; Peter B. Reich; Bernhard Schmid; Nawal Shrestha; Xiao Feng; Tong Lyu; Brian S. Maitner; Xiaoting Xu; Yichao Li; Dongting Zou; Zheng‐Hong Tan; Xiangyan Su; et al. (Ecology Letters, 2020)
A key challenge in ecology is to understand the relationships between organismal traits and ecosystem processes. Here, with a novel dataset of leaf length and width for 10 480 woody dicots in China and 2374 in North America, we show that the variation in community mean leaf size is highly correlated with the variation in climate and ecosystem primary productivity, independent of plant life form. These relationships likely reflect how natural selection modifies leaf size across varying climates in conjunction with how climate influences canopy total leaf area. We find that the leaf size‒primary productivity functions based on the Chinese dataset can predict productivity in North America and vice‐versa. In addition to advancing understanding of the relationship between a climate‐driven trait and ecosystem functioning, our findings suggest that leaf size can also be a promising tool in palaeoecology for scaling from fossil leaves to palaeo‐primary productivity of woody ecosystems.

Species' range model metadata standards: RMMS - Cory Merow; Brian S. Maitner; Hannah L. Owens; Jamie M. Kass; Brian J. Enquist; Walter Jetz; Rob Guralnick (Global Ecology and Biogeography, 2019)
Aim The geographic range and ecological niche of species are widely used concepts in ecology, evolution and conservation and many modelling approaches have been developed to quantify each. Niche and distribution modelling methods require a litany of design choices; differences among subdisciplines have created communication barriers that increase isolation of scientific advances. As a result, understanding and reproducing the work of others is difficult, if not impossible. It is often challenging to evaluate whether a model has been built appropriately for its intended application or subsequent reuse. Here, we propose a standardized model metadata framework that enables researchers to understand and evaluate modelling decisions while making models fully citable and reproducible. Such reproducibility is critical for both scientific and policy reports, while international standardization enables better comparison between different scenarios and research groups. Innovation Range modelling metadata (RMMS) address three challenges: they (a) are designed for convenience to encourage use, (b) accommodate a wide variety of applications, and (c) are extensible to allow the research community to steer them as needed. RMMS are based on a metadata dictionary that specifies a hierarchical structure to catalogue different aspects of the range modelling process. The dictionary balances a constrained, minimalist vocabulary to improve standardization with flexibility for users to modify and extend. To facilitate use, we have developed an R package, rangeModelMetaData , to build templates, automatically fill values from common modelling objects, check for inconsistencies with standards, and suggest values. Main conclusions Range Modelling Metadata tools foster cross‐disciplinary advances in biogeography, conservation and allied disciplines by improving evaluation, model sharing, model searching, comparisons and reproducibility among studies. Our initially proposed standards here are designed to be modified and extended to evolve with research trends and needs.

Temperature shapes opposing latitudinal gradients of plant taxonomic and phylogenetic β diversity - Ian R. McFadden; Brody Sandel; Constantinos Tsirogiannis; Naia Morueta‐Holme; Jens‐Christian Svenning; Brian J. Enquist; Nathan J.B. Kraft (Ecology Letters, 2019)
Latitudinal and elevational richness gradients have received much attention from ecologists but there is little consensus on underlying causes. One possible proximate cause is increased levels of species turnover, or β diversity, in the tropics compared to temperate regions. Here, we leverage a large botanical dataset to map taxonomic and phylogenetic β diversity, as mean turnover between neighboring 100 × 100 km cells, across the Americas and determine key climatic drivers. We find taxonomic and tip‐weighted phylogenetic β diversity is higher in the tropics, but that basal‐weighted phylogenetic β diversity is highest in temperate regions. Supporting Janzen's ‘mountain passes’ hypothesis, tropical mountainous regions had higher β diversity than temperate regions for taxonomic and tip‐weighted metrics. The strongest climatic predictors of turnover were average temperature and temperature seasonality. Taken together, these results suggest β diversity is coupled to latitudinal richness gradients and that temperature is a major driver of plant community composition and change.

Drier tropical forests are susceptible to functional changes in response to a long‐term drought - Jesús Aguirre‐Gutiérrez; Imma Oliveras; Sami Rifai; Sophie Fauset; Stephen Adu‐Bredu; Kofi Affum‐Baffoe; Timothy R. Baker; Ted R. Feldpausch; Agne Gvozdevaite; Wannes Hubau; Nathan J. B. Kraft; Simon L. Lewis; et al. (Ecology Letters, 2019)
Climatic changes have profound effects on the distribution of biodiversity, but untangling the links between climatic change and ecosystem functioning is challenging, particularly in high diversity systems such as tropical forests. Tropical forests may also show different responses to a changing climate, with baseline climatic conditions potentially inducing differences in the strength and timing of responses to droughts. Trait‐based approaches provide an opportunity to link functional composition, ecosystem function and environmental changes. We demonstrate the power of such approaches by presenting a novel analysis of long‐term responses of different tropical forest to climatic changes along a rainfall gradient. We explore how key ecosystem's biogeochemical properties have shifted over time as a consequence of multi‐decadal drying. Notably, we find that drier tropical forests have increased their deciduous species abundance and generally changed more functionally than forests growing in wetter conditions, suggesting an enhanced ability to adapt ecologically to a drying environment.

Late Quaternary climate legacies in contemporary plant functional composition - Benjamin Blonder; Brian J. Enquist; Bente J. Graae; Jens Kattge; Brian S. Maitner; Naia Morueta‐Holme; Alejandro Ordonez; Irena Šímová; Joy Singarayer; Jens‐Christian Svenning; Paul J. Valdes; Cyrille Violle (Global Change Biology, 2018)
The functional composition of plant communities is commonly thought to be determined by contemporary climate. However, if rates of climate‐driven immigration and/or exclusion of species are slow, then contemporary functional composition may be explained by paleoclimate as well as by contemporary climate. We tested this idea by coupling contemporary maps of plant functional trait composition across North and South America to paleoclimate means and temporal variation in temperature and precipitation from the Last Interglacial (120 ka) to the present. Paleoclimate predictors strongly improved prediction of contemporary functional composition compared to contemporary climate predictors, with a stronger influence of temperature in North America (especially during periods of ice melting) and of precipitation in South America (across all times). Thus, climate from tens of thousands of years ago influences contemporary functional composition via slow assemblage dynamics.

Spatial patterns and climate relationships of major plant traits in the New World differ between woody and herbaceous species - Irena Šímová; Cyrille Violle; Jens‐Christian Svenning; Jens Kattge; Kristine Engemann; Brody Sandel; Robert K. Peet; Susan K. Wiser; Benjamin Blonder; Brian J. McGill; Brad Boyle; Naia Morueta‐Holme; et al. (Journal of Biogeography, 2018)
Aim Despite several recent efforts to map plant traits and to identify their climatic drivers, there are still major gaps. Global trait patterns for major functional groups, in particular, the differences between woody and herbaceous plants, have yet to be identified. Here, we take advantage of big data efforts to compile plant species occurrence and trait data to analyse the spatial patterns of assemblage means and variances of key plant traits. We tested whether these patterns and their climatic drivers are similar for woody and herbaceous plants. Location New World (North and South America). Methods Using the largest currently available database of plant occurrences, we provide maps of 200 × 200 km grid‐cell trait means and variances for both woody and herbaceous species and identify environmental drivers related to these patterns. We focus on six plant traits: maximum plant height, specific leaf area, seed mass, wood density, leaf nitrogen concentration and leaf phosphorus concentration. Results For woody assemblages, we found a strong climate signal for both means and variances of most of the studied traits, consistent with strong environmental filtering. In contrast, for herbaceous assemblages, spatial patterns of trait means and variances were more variable, the climate signal on trait means was often different and weaker. Main conclusion Trait variations for woody versus herbaceous assemblages appear to reflect alternative strategies and differing environmental constraints. Given that most large‐scale trait studies are based on woody species, the strikingly different biogeographic patterns of herbaceous traits suggest that a more synthetic framework is needed that addresses how suites of traits within and across broad functional groups respond to climate.

Draining the Pool? Carbon Storage and Fluxes in Three Alpine Plant Communities - Mia Vedel Sørensen; Richard Strimbeck; Kristin Odden Nystuen; Rozalia Erzsebet Kapas; Brian J. Enquist; Bente Jessen Graae (Ecosystems, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Taxonomic decomposition of the latitudinal gradient in species diversity of North American floras - Michael D. Weiser; Nathan G. Swenson; Brian J. Enquist; Sean T. Michaletz; Robert B. Waide; Jizhong Zhou; Michael Kaspari (Journal of Biogeography, 2018)
Aim To test the latitudinal gradient in plant species diversity for self‐similarity across taxonomic scales and amongst taxa. Location North America. Methods We used species richness data from 245 local vascular plant floras to quantify the slope and shape of the latitudinal gradients in species diversity ( LGSD ) across all plant species as well as within each family and order. We calculated the contribution of each family and order to the empirical LGSD . Results We observed the canonical LGSD when all plants were considered with floras at the lowest latitudes having, on average, 451 more species than floras at the highest latitudes. When considering slope alone, most orders and families showed the expected negative slope, but 31.7% of families and 27.7% of orders showed either no significant relationship between latitude and diversity or a reverse LGSD . Latitudinal patterns of family diversity account for at least 14% of this LGSD . Most orders and families did not show the negative slope and concave‐down quadratic shape expected by the pattern for all plant species. A majority of families did not make a significant contribution in species to the LGSD with 53% of plant families contributing little to nothing to the overall gradient. Ten families accounted for more than 70% of the gradient. Two families, the Asteraceae and Fabaceae, contributed a third of the LGSD . Main Conclusions The empirical LGSD we describe here is a consequence of a gradient in the number of families and diversification within relative few plant families. Macroecological studies typically aim to generate models that are general across taxa with the implicit assumption that the models are general within taxa. Our results strongly suggest that models of the latitudinal gradient in plant species richness that rely on environmental covariates (e.g. temperature, energy) are likely not general across plant taxa.

Drivers of terrestrial plant production across broad geographical gradients - Sean T. Michaletz; Andrew J. Kerkhoff; Brian J. Enquist (Global Ecology and Biogeography, 2018)
Terrestrial net primary production (NPP) varies across global climate gradients, but the mechanisms through which climate drives this variation remain subject to debate. Specifically, it is debatable whether NPP is primarily influenced by ‘direct’ effects of climate on the kinetics of plant metabolism or ‘indirect’ effects of climate on plant size, stand biomass, stand age structure and growing season length. We clarify several issues in this debate by presenting multiple lines of evidence that support a primarily indirect influence of climate on global variation in NPP across broad geographical gradients. First, we highlight > 60 years of research that suggests leaf area, growing season length, plant biomass and/or plant age are better predictors of NPP than climate or latitude. Second, we refute recent claims that using biomass and age as predictors of NPP represents circular reasoning. Third, we illustrate why effects of climate on the kinetics of plant production must be evaluated using instantaneous (not annualized) rates of productivity. Fourth, we review recent analyses showing that the effects of biomass and age on NPP are much stronger than the effects of climate. Fifth, we present new analyses of a high‐quality NPP dataset that demonstrate further that biomass, age and growing season length are better predictors of global variation in NPP than climate variables. Our results are consistent with the hypothesis that variation in NPP across global climate gradients primarily reflects the influence of climate on growing season length and stand biomass, as well as stand age, rather than the effects of temperature and precipitation on the kinetics of metabolism. However, this hypothesis should be evaluated further using larger, high‐quality observational and experimental datasets spanning multiple geographical scales.

Fire effects and ecological recovery pathways of tropical montane cloud forests along a time chronosequence - Imma Oliveras; Rosa M. Román‐Cuesta; Erickson Urquiaga‐Flores; Jose A. Quintano Loayza; Jose Kala; Vicky Huamán; Nohemi Lizárraga; Guissela Sans; Katia Quispe; Efrain Lopez; David Lopez; Israel Cuba Torres; et al. (Global Change Biology, 2018)
Tropical montane cloud forests ( TMCF s) harbour high levels of biodiversity and large carbon stocks. Their location at high elevations make them especially sensitive to climate change, because a warming climate is enhancing upslope species migration, but human disturbance (especially fire) may in many cases be pushing the treeline downslope. TMCF s are increasingly being affected by fire, and the long‐term effects of fire are still unknown. Here, we present a 28‐year chronosequence to assess the effects of fire and recovery pathways of burned TMCF s, with a detailed analysis of carbon stocks, forest structure and diversity. We assessed rates of change of carbon (C) stock pools, forest structure and tree‐size distribution pathways and tested several hypotheses regarding metabolic scaling theory ( MST ), C recovery and biodiversity. We found four different C stock recovery pathways depending on the selected C pool and time since last fire, with a recovery of total C stocks but not of aboveground C stocks. In terms of forest structure, there was an increase in the number of small stems in the burned forests up to 5–9 years after fire because of regeneration patterns, but no differences on larger trees between burned and unburned plots in the long term. In support of MST , after fire, forest structure appears to approximate steady‐state size distribution in less than 30 years. However, our results also provide new evidence that the species recovery of TMCF after fire is idiosyncratic and follows multiple pathways. While fire increased species richness, it also enhanced species dissimilarity with geographical distance. This is the first study to report a long‐term chronosequence of recovery pathways to fire suggesting faster recovery rates than previously reported, but at the expense of biodiversity and aboveground C stocks.

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

Assessing trait‐based scaling theory in tropical forests spanning a broad temperature gradient - Brian J. Enquist; Lisa Patrick Bentley; Alexander Shenkin; Brian Maitner; Van Savage; Sean Michaletz; Benjamin Blonder; Vanessa Buzzard; Tatiana Erika Boza Espinoza; William Farfan‐Rios; Christopher E. Doughty; Gregory R. Goldsmith; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical elevation gradients are natural laboratories to assess how changing climate can influence tropical forests. However, there is a need for theory and integrated data collection to scale from traits to ecosystems. We assess predictions of a novel trait‐based scaling theory, including whether observed shifts in forest traits across a broad tropical temperature gradient are consistent with local phenotypic optima and adaptive compensation for temperature. Location An elevation gradient spanning 3,300 m and consisting of thousands of tropical tree trait measures taken from 16 1‐ha tropical forest plots in southern Perú, where gross and net primary productivity (GPP and NPP) were measured. Time period April to November 2013. Major taxa studied Plants; tropical trees. Methods We developed theory to scale from traits to communities and ecosystems and tested several predictions. We assessed the covariation between climate, traits, biomass and GPP and NPP. We measured multiple traits linked to variation in tree growth and assessed their frequency distributions within and across the elevation gradient. We paired these trait measures across individuals within 16 forests with simultaneous measures of ecosystem net and gross primary productivity. Results Consistent with theory, variation in forest NPP and GPP primarily scaled with forest biomass, but the secondary effect of temperature on productivity was much less than expected. This weak temperature dependence appears to reflect directional shifts in several mean community traits that underlie tree growth with decreases in site temperature. Main conclusions The observed shift in traits of trees that dominate in more cold environments is consistent with an ‘adaptive/acclimatory’ compensation for the kinetic effects of temperature on leaf photosynthesis and tree growth. Forest trait distributions across the gradient showed overly peaked and skewed distributions, consistent with the importance of local filtering of optimal growth traits and recent shifts in species composition and dominance attributable to warming from climate change. Trait‐based scaling theory provides a basis to predict how shifts in climate have and will influence the trait composition and ecosystem functioning of tropical forests.

Using n ‐dimensional hypervolumes for species distribution modelling: A response to Qiao et al. () - Benjamin Blonder; Christine Lamanna; Cyrille Violle; Brian J. Enquist (Global Ecology and Biogeography, 2017)
Hypervolume approaches are used to quantify functional diversity and quantify environmental niches for species distribution modelling. Recently, Qiao et al. ( ) criticized our geometrical kernel density estimation (KDE) method for measuring hypervolumes. They used a simulation analysis to argue that the method yields high error rates and makes biased estimates of fundamental niches. Here, we show that (a) KDE output depends in useful ways on dataset size and bias, (b) other species distribution modelling methods make equally stringent but different assumptions about dataset bias, (c) simulation results presented by Qiao et al. ( ) were incorrect, with revised analyses showing performance comparable to other methods, and (d) hypervolume methods are more general than KDE and have other benefits for niche modelling. As a result, our KDE method remains a promising tool for species distribution modelling.

Less favourable climates constrain demographic strategies in plants - Anna M. Csergő; Roberto Salguero‐Gómez; Olivier Broennimann; Shaun R. Coutts; Antoine Guisan; Amy L. Angert; Erik Welk; Iain Stott; Brian J. Enquist; Brian McGill; Jens‐Christian Svenning; Cyrille Violle; et al. (Ecology Letters, 2017)
Correlative species distribution models are based on the observed relationship between species’ occurrence and macroclimate or other environmental variables. In climates predicted less favourable populations are expected to decline, and in favourable climates they are expected to persist. However, little comparative empirical support exists for a relationship between predicted climate suitability and population performance. We found that the performance of 93 populations of 34 plant species worldwide – as measured by in situ population growth rate, its temporal variation and extinction risk – was not correlated with climate suitability. However, correlations of demographic processes underpinning population performance with climate suitability indicated both resistance and vulnerability pathways of population responses to climate: in less suitable climates, plants experienced greater retrogression (resistance pathway) and greater variability in some demographic rates (vulnerability pathway). While a range of demographic strategies occur within species’ climatic niches, demographic strategies are more constrained in climates predicted to be less suitable.

Biogeochemistry drives diversity in the prokaryotes, fungi, and invertebrates of a Panama forest - Michael Kaspari; Jelena Bujan; Michael D. Weiser; Daliang Ning; Sean T. Michaletz; He Zhili; Brian J. Enquist; Robert B. Waide; Jizhong Zhou; Benjamin L. Turner; S. Joseph Wright (Ecology, 2017)
Humans are both fertilizing the world and depleting its soils, decreasing the diversity of aquatic ecosystems and terrestrial plants in the process. We know less about how nutrients shape the abundance and diversity of the prokaryotes, fungi, and invertebrates of Earth's soils. Here we explore this question in the soils of a Panama forest subject to a 13‐yr fertilization with factorial combinations of nitrogen (N), phosphorus (P), and potassium (K) and a separate micronutrient cocktail. We contrast three hypotheses linking biogeochemistry to abundance and diversity. Consistent with the Stress Hypothesis, adding N suppressed the abundance of invertebrates and the richness of all three groups of organisms by ca. 1 SD or more below controls. Nitrogen addition plots were 0.8 pH units more acidic with 18% more exchangeable aluminum, which is toxic to both prokaryotes and eukaryotes. These stress effects were frequently reversed, however, when N was added with P (for prokaryotes and invertebrates) and with added K (for fungi). Consistent with the Abundance Hypothesis, adding P generally increased prokaryote and invertebrate diversity, and adding K enhanced invertebrate diversity. Also consistent with the Abundance Hypothesis, increases in invertebrate abundance generated increases in richness. We found little evidence for the Competition Hypothesis: that single nutrients suppressed diversity by favoring a subset of high nutrient specialists, and that nutrient combinations suppressed diversity even more. Instead, combinations of nutrients, and especially the cation/micronutrient treatment, yielded the largest increases in richness in the two eukaryote groups. In sum, changes in soil biogeochemistry revealed a diversity of responses among the three dominant soil groups, positive synergies among nutrients, and–in contrast with terrestrial plants–the frequent enhancement of soil biodiversity.

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

Solar radiation and functional traits explain the decline of forest primary productivity along a tropical elevation gradient - Nikolaos M. Fyllas; Lisa Patrick Bentley; Alexander Shenkin; Gregory P. Asner; Owen K. Atkin; Sandra Díaz; Brian J. Enquist; William Farfan‐Rios; Emanuel Gloor; Rossella Guerrieri; Walter Huaraca Huasco; Yoko Ishida; et al. (Ecology Letters, 2017)
One of the major challenges in ecology is to understand how ecosystems respond to changes in environmental conditions, and how taxonomic and functional diversity mediate these changes. In this study, we use a trait‐spectra and individual‐based model, to analyse variation in forest primary productivity along a 3.3 km elevation gradient in the Amazon‐Andes. The model accurately predicted the magnitude and trends in forest productivity with elevation, with solar radiation and plant functional traits (leaf dry mass per area, leaf nitrogen and phosphorus concentration, and wood density) collectively accounting for productivity variation. Remarkably, explicit representation of temperature variation with elevation was not required to achieve accurate predictions of forest productivity, as trait variation driven by species turnover appears to capture the effect of temperature. Our semi‐mechanistic model suggests that spatial variation in traits can potentially be used to estimate spatial variation in productivity at the landscape scale.

Predicting trait‐environment relationships for venation networks along an Andes‐Amazon elevation gradient - Benjamin Blonder; Norma Salinas; Lisa Patrick Bentley; Alexander Shenkin; Percy O. Chambi Porroa; Yolvi Valdez Tejeira; Cyrille Violle; Nikolaos M. Fyllas; Gregory R. Goldsmith; Roberta E. Martin; Gregory P. Asner; Sandra Díaz; et al. (Ecology, 2017)
Understanding functional trait‐environment relationships ( TER s) may improve predictions of community assembly. However, many empirical TER s have been weak or lacking conceptual foundation. TER s based on leaf venation networks may better link individuals and communities via hydraulic constraints. We report measurements of vein density, vein radius, and leaf thickness for more than 100 dominant species occurring in ten forest communities spanning a 3,300 m Andes‐Amazon elevation gradient in Peru. We use these data to measure the strength of TER s at community scale and to determine whether observed TER s are similar to those predicted by physiological theory. We found strong support for TER s between all traits and temperature, as well weaker support for a predicted TER between maximum abundance‐weighted leaf transpiration rate and maximum potential evapotranspiration. These results provide one approach for developing a more mechanistic trait‐based community assembly theory.

Predictability in community dynamics - Benjamin Blonder; Derek E. Moulton; Jessica Blois; Brian J. Enquist; Bente J. Graae; Marc Macias‐Fauria; Brian McGill; Sandra Nogué; Alejandro Ordonez; Brody Sandel; Jens‐Christian Svenning (Ecology Letters, 2017)
The coupling between community composition and climate change spans a gradient from no lags to strong lags. The no‐lag hypothesis is the foundation of many ecophysiological models, correlative species distribution modelling and climate reconstruction approaches. Simple lag hypotheses have become prominent in disequilibrium ecology, proposing that communities track climate change following a fixed function or with a time delay. However, more complex dynamics are possible and may lead to memory effects and alternate unstable states. We develop graphical and analytic methods for assessing these scenarios and show that these dynamics can appear in even simple models. The overall implications are that (1) complex community dynamics may be common and (2) detailed knowledge of past climate change and community states will often be necessary yet sometimes insufficient to make predictions of a community's future state.

Observed forest sensitivity to climate implies large changes in 21st century North American forest growth - Noah D. Charney; Flurin Babst; Benjamin Poulter; Sydne Record; Valerie M. Trouet; David Frank; Brian J. Enquist; Margaret E. K. Evans (Ecology Letters, 2016)
Predicting long‐term trends in forest growth requires accurate characterisation of how the relationship between forest productivity and climatic stress varies across climatic regimes. Using a network of over two million tree‐ring observations spanning North America and a space‐for‐time substitution methodology, we forecast climate impacts on future forest growth. We explored differing scenarios of increased water‐use efficiency ( WUE ) due to CO 2 ‐fertilisation, which we simulated as increased effective precipitation. In our forecasts: (1) climate change negatively impacted forest growth rates in the interior west and positively impacted forest growth along the western, southeastern and northeastern coasts; (2) shifting climate sensitivities offset positive effects of warming on high‐latitude forests, leaving no evidence for continued ‘boreal greening’; and (3) it took a 72% WUE enhancement to compensate for continentally averaged growth declines under RCP 8.5. Our results highlight the importance of locally adapted forest management strategies to handle regional differences in growth responses to climate change.

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Assessing the general patterns of forest structure: quantifying tree and forest allometric scaling relationships in the U nited S tates - Laura I. Duncanson; Ralph O. Dubayah; Brian J. Enquist (Global Ecology and Biogeography, 2015)
Aim Understanding the drivers of forest structure, function and change is a fundamental problem in both theoretical ecology and applied forestry for carbon mapping and monitoring. An important component of forest ecology research often utilizes allometric equations to scale up local measurements to predict large‐scale forest and ecosystem‐level properties. However, both applied and theoretical allometries in forest ecology (such as metabolic scaling theory, MST ) assume that many scaling relationships are insensitive to broad‐scale climate gradients or species life histories. We aim to test these assumptions by mapping continental‐scale forest allometry across environmental gradients in the U nited S tates. Location U nited S tates. Methods We fit exponents to two allometric relationships in c . 100,000 F orest I nventory A nalysis ( FIA ) field plots: (1) the relationship between the height of an individual tree and its diameter, and (2) plot‐level tree size distributions. We compare fitted exponents to environmental and life‐history variables, such as climate, topography and forest structure, in an attempt to explain allometric variability and deviations from theoretically predicted allometries. Results We find that the structural allometry of forests varies strongly as a function of location in the U nited S tates. Allometric exponents appear to asymptote at approximately where MST theory predicts with increasing forest height, while deviations from MST are partially explained as a function of environmentally driven recruitment limitations and successional status. Main conclusions While we find support for invariant tree and stand allometric scaling relationships in forests that are in steady state with regard to demography and resources, we also find considerable spatial variability in forest allometric relationships when steady‐state conditions are violated. These findings suggest that extensions of metabolic scaling theory should incorporate variation in demographic dynamics in younger successional forests, and factors influencing recruitment limitation.

Linking canopy leaf area and light environments with tree size distributions to explain Amazon forest demography - Scott C. Stark; Brian J. Enquist; Scott R. Saleska; Veronika Leitold; Juliana Schietti; Marcos Longo; Luciana F. Alves; Plinio B. Camargo; Raimundo C. Oliveira (Ecology Letters, 2015)
Forest biophysical structure – the arrangement and frequency of leaves and stems – emerges from growth, mortality and space filling dynamics, and may also influence those dynamics by structuring light environments. To investigate this interaction, we developed models that could use LiDAR remote sensing to link leaf area profiles with tree size distributions, comparing models which did not (metabolic scaling theory) and did allow light to influence this link. We found that a light environment‐to‐structure link was necessary to accurately simulate tree size distributions and canopy structure in two contrasting Amazon forests. Partitioning leaf area profiles into size‐class components, we found that demographic rates were related to variation in light absorption, with mortality increasing relative to growth in higher light, consistent with a light environment feedback to size distributions. Combining LiDAR with models linking forest structure and demography offers a high‐throughput approach to advance theory and investigate climate‐relevant tropical forest change.

The Effect of the Foresummer Drought on Carbon Exchange in Subalpine Meadows - Lindsey L. Sloat; Amanda N. Henderson; Christine Lamanna; Brian J. Enquist (Ecosystems, 2015)

Linking environmental filtering and disequilibrium to biogeography with a community climate framework - Benjamin Blonder; David Nogués-Bravo; Michael K. Borregaard; John C. Donoghue II; Peter M. Jørgensen; Nathan J. B. Kraft; Jean-Philippe Lessard; Naia Morueta-Holme; Brody Sandel; Jens-Christian Svenning; Cyrille Violle; Carsten Rahbek; et al. (Ecology, 2015)
We present a framework to measure the strength of environmental filtering and disequilibrium of the species composition of a local community across time, relative to past, current, and future climates. We demonstrate the framework by measuring the impact of climate change on New World forests, integrating data for climate niches of more than 14 000 species, community composition of 471 New World forest plots, and observed climate across the most recent glacial–interglacial interval. We show that a majority of communities have species compositions that are strongly filtered and are more in equilibrium with current climate than random samples from the regional pool. Variation in the level of current community disequilibrium can be predicted from Last Glacial Maximum climate and will increase with near‐future climate change.

Ecological traits influence the phylogenetic structure of bird species co‐occurrences worldwide - Jean‐Yves Barnagaud; W. Daniel Kissling; Brody Sandel; Wolf L. Eiserhardt; Çağan H. Şekercioğlu; Brian J. Enquist; Constantinos Tsirogiannis; Jens‐Christian Svenning (Ecology Letters, 2014)
The extent to which species’ ecological and phylogenetic relatedness shape their co‐occurrence patterns at large spatial scales remains poorly understood. By quantifying phylogenetic assemblage structure within geographic ranges of >8000 bird species, we show that global co‐occurrence patterns are linked – after accounting for regional effects – to key ecological traits reflecting diet, mobility, body size and climatic preference. We found that co‐occurrences of carnivorous, migratory and cold‐climate species are phylogenetically clustered, whereas nectarivores, herbivores, frugivores and invertebrate eaters tend to be more phylogenetically overdispersed. Preference for open or forested habitats appeared to be independent from the level of phylogenetic clustering. Our results advocate for an extension of the tropical niche conservatism hypothesis to incorporate ecological and life‐history traits beyond the climatic niche. They further offer a novel species‐oriented perspective on how biogeographic and evolutionary legacies interact with ecological traits to shape global patterns of species coexistence in birds.

The n ‐dimensional hypervolume - Benjamin Blonder; Christine Lamanna; Cyrille Violle; Brian J. Enquist (Global Ecology and Biogeography, 2014)
Aim The Hutchinsonian hypervolume is the conceptual foundation for many lines of ecological and evolutionary inquiry, including functional morphology, comparative biology, community ecology and niche theory. However, extant methods to sample from hypervolumes or measure their geometry perform poorly on high‐dimensional or holey datasets. Innovation We first highlight the conceptual and computational issues that have prevented a more direct approach to measuring hypervolumes. Next, we present a new multivariate kernel density estimation method that resolves many of these problems in an arbitrary number of dimensions. Main conclusions We show that our method (implemented as the ‘hypervolume’ R package) can match several extant methods for hypervolume geometry and species distribution modelling. Tools to quantify high‐dimensional ecological hypervolumes will enable a wide range of fundamental descriptive, inferential and comparative questions to be addressed.

Habitat area and climate stability determine geographical variation in plant species range sizes - Naia Morueta‐Holme; Brian J. Enquist; Brian J. McGill; Brad Boyle; Peter M. Jørgensen; Jeffrey E. Ott; Robert K. Peet; Irena Šímová; Lindsey L. Sloat; Barbara Thiers; Cyrille Violle; Susan K. Wiser; et al. (Ecology Letters, 2013)
Despite being a fundamental aspect of biodiversity, little is known about what controls species range sizes. This is especially the case for hyperdiverse organisms such as plants. We use the largest botanical data set assembled to date to quantify geographical variation in range size for ~ 85 000 plant species across the New World. We assess prominent hypothesised range‐size controls, finding that plant range sizes are codetermined by habitat area and long‐ and short‐term climate stability. Strong short‐ and long‐term climate instability in large parts of North America, including past glaciations, are associated with broad‐ranged species. In contrast, small habitat areas and a stable climate characterise areas with high concentrations of small‐ranged species in the Andes, Central America and the Brazilian Atlantic Rainforest region. The joint roles of area and climate stability strengthen concerns over the potential effects of future climate change and habitat loss on biodiversity.

An empirical assessment of tree branching networks and implications for plant allometric scaling models - Lisa Patrick Bentley; James C. Stegen; Van M. Savage; Duncan D. Smith; Erica I. von Allmen; John S. Sperry; Peter B. Reich; Brian J. Enquist (Ecology Letters, 2013)
Several theories predict whole‐tree function on the basis of allometric scaling relationships assumed to emerge from traits of branching networks. To test this key assumption, and more generally, to explore patterns of external architecture within and across trees, we measure branch traits (radii/lengths) and calculate scaling exponents from five functionally divergent species. Consistent with leading theories, including metabolic scaling theory, branching is area preserving and statistically self‐similar within trees. However, differences among scaling exponents calculated at node‐ and whole‐tree levels challenge the assumption of an optimised, symmetrically branching tree. Furthermore, scaling exponents estimated for branch length change across branching orders, and exponents for scaling metabolic rate with plant size (or number of terminal tips) significantly differ from theoretical predictions. These findings, along with variability in the scaling of branch radii being less than for branch lengths, suggest extending current scaling theories to include asymmetrical branching and differential selective pressures in plant architectures.

A common genetic basis to the origin of the leaf economics spectrum and metabolic scaling allometry - François Vasseur; Cyrille Violle; Brian J. Enquist; Christine Granier; Denis Vile (Ecology Letters, 2012)
Many facets of plant form and function are reflected in general cross‐taxa scaling relationships. Metabolic scaling theory ( MST ) and the leaf economics spectrum ( LES ) have each proposed unifying frameworks and organisational principles to understand the origin of botanical diversity. Here, we test the evolutionary assumptions of MST and the LES using a cross of two genetic variants of Arabidopsis thaliana . We show that there is enough genetic variation to generate a large fraction of variation in the LES and MST scaling functions. The progeny sharing the parental, naturally occurring, allelic combinations at two pleiotropic genes exhibited the theorised optimum ¾ allometric scaling of growth rate and intermediate leaf economics. Our findings: (1) imply that a few pleiotropic genes underlie many plant functional traits and life histories; (2) unify MST and LES within a common genetic framework and (3) suggest that observed intermediate size and longevity in natural populations originate from stabilising selection to optimise physiological trade‐offs.

The Adaptation for Conservation Targets (ACT) Framework: A Tool for Incorporating Climate Change into Natural Resource Management - Molly S. Cross; Erika S. Zavaleta; Dominique Bachelet; Marjorie L. Brooks; Carolyn A. F. Enquist; Erica Fleishman; Lisa J. Graumlich; Craig R. Groves; Lee Hannah; Lara Hansen; Greg Hayward; Marni Koopman; et al. (Environmental Management, 2012)

The biogeography and filtering of woody plant functional diversity in North and South America - Nathan G. Swenson; Brian J. Enquist; Jason Pither; Andrew J. Kerkhoff; Brad Boyle; Michael D. Weiser; James J. Elser; William F. Fagan; Jimena Forero‐Montaña; Nikolaos Fyllas; Nathan J. B. Kraft; Jeffrey K. Lake; et al. (Global Ecology and Biogeography, 2012)
Aim In recent years evidence has accumulated that plant species are differentially sorted from regional assemblages into local assemblages along local‐scale environmental gradients on the basis of their function and abiotic filtering. The favourability hypothesis in biogeography proposes that in climatically difficult regions abiotic filtering should produce a regional assemblage that is less functionally diverse than that expected given the species richness and the global pool of traits. Thus it seems likely that differential filtering of plant traits along local‐scale gradients may scale up to explain the distribution, diversity and filtering of plant traits in regional‐scale assemblages across continents. The present work aims to address this prediction. Location North and South America. Methods We combine a dataset comprising over 5.5 million georeferenced plant occurrence records with several large plant functional trait databases in order to: (1) quantify how several critical traits associated with plant performance and ecology vary across environmental gradients; and (2) provide the first test of whether the woody plants found within 1° and 5° map grid cells are more or less functionally diverse than expected, given their species richness, across broad gradients. Results The results show that, for many of the traits studied, the overall distribution of functional traits in tropical regions often exceeds the expectations of random sampling given the species richness. Conversely, temperate regions often had narrower functional trait distributions than their smaller species pools would suggest. Main conclusion The results show that the overall distribution of function does increase towards the equator, but the functional diversity within regional‐scale tropical assemblages is higher than that expected given their species richness. These results are consistent with the hypothesis that abiotic filtering constrains the overall distribution of function in temperate assemblages, but tropical assemblages are not as tightly constrained.

Interannual variability of growth and reproduction in Bursera simaruba : the role of allometry and resource variability - Catherine M. Hulshof; James C. Stegen; Nathan G. Swenson; Carolyn A. F. Enquist; Brian J. Enquist (Ecology, 2012)
Plants are expected to differentially allocate resources to reproduction, growth, and survival in order to maximize overall fitness. Life history theory predicts that the allocation of resources to reproduction should occur at the expense of vegetative growth. Although it is known that both organism size and resource availability can influence life history traits, few studies have addressed how size dependencies of growth and reproduction and variation in resource supply jointly affect the coupling between growth and reproduction. In order to understand the relationship between growth and reproduction in the context of resource variability, we utilize a long‐term observational data set consisting of 670 individual trees over a 10‐year period within a local population of Bursera simaruba (L.) Sarg. We (1) quantify the functional form and variability in the growth–reproduction relationship at the population and individual‐tree level and (2) develop a theoretical framework to understand the allometric dependence of growth and reproduction. Our findings suggest that the differential responses of allometric growth and reproduction to resource availability, both between years and between microsites, underlie the apparent relationship between growth and reproduction. Finally, we offer an alternative approach for quantifying the relationship between growth and reproduction that accounts for variation in allometries.

Venation networks and the origin of the leaf economics spectrum - Benjamin Blonder; Cyrille Violle; Lisa Patrick Bentley; Brian J. Enquist (Ecology Letters, 2011)
Ecology Letters (2011) 14: 91–100 Abstract The leaf economics spectrum describes biome‐invariant scaling functions for leaf functional traits that relate to global primary productivity and nutrient cycling. Here, we develop a comprehensive framework for the origin of this leaf economics spectrum based on venation‐mediated economic strategies. We define a standardized set of traits – density, distance and loopiness – that provides a common language for the study of venation. We develop a novel quantitative model that uses these venation traits to model leaf‐level physiology, and show that selection to optimize the venation network predicts the mean global trait–trait scaling relationships across 2548 species. Furthermore, using empirical venation data for 25 plant species, we test our model by predicting four key leaf functional traits related to leaf economics: net carbon assimilation rate, life span, leaf mass per area ratio and nitrogen content. Together, these results indicate that selection on venation geometry is a fundamental basis for understanding the diversity of leaf form and function, and the carbon balance of leaves. The model and associated predictions have broad implications for integrating venation network geometry with pattern and process in ecophysiology, ecology and palaeobotany.

U.S. Natural Resources and Climate Change: Concepts and Approaches for Management Adaptation - Jordan M. West; Susan H. Julius; Peter Kareiva; Carolyn Enquist; Joshua J. Lawler; Brian Petersen; Ayana E. Johnson; M. Rebecca Shaw (Environmental Management, 2009)

Advancing the metabolic theory of biodiversity - James C. Stegen; Brian J. Enquist; Regis Ferriere (Ecology Letters, 2009)
A component of metabolic scaling theory has worked towards understanding the influence of metabolism over the generation and maintenance of biodiversity. Specific models within this ‘metabolic theory of biodiversity’ (MTB) have addressed temperature gradients in speciation rate and species richness, but the scope of MTB has been questioned because of empirical departures from model predictions. In this study, we first show that a generalized MTB is not inconsistent with empirical patterns and subsequently implement an eco‐evolutionary MTB which has thus far only been discussed qualitatively. More specifically, we combine a functional trait (body mass) approach and an environmental gradient (temperature) with a dynamic eco‐evolutionary model that builds on the current MTB. Our approach uniquely accounts for feedbacks between ecological interactions (size‐dependent competition and predation) and evolutionary rates (speciation and extinction). We investigate a simple example in which temperature influences mutation rate, and show that this single effect leads to dynamic temperature gradients in macroevolutionary rates and community structure. Early in community evolution, temperature strongly influences speciation and both speciation and extinction strongly influence species richness. Through time, niche structure evolves, speciation and extinction rates fall, and species richness becomes increasingly independent of temperature. However, significant temperature‐richness gradients may persist within emergent functional (trophic) groups, especially when niche breadths are wide. Thus, there is a strong signal of both history and ecological interactions on patterns of species richness across temperature gradients. More generally, the successful implementation of an eco‐evolutionary MTB opens the perspective that a process‐based MTB can continue to emerge through further development of metabolic models that are explicit in terms of functional traits and environmental gradients.

Above‐ground forest biomass is not consistently related to wood density in tropical forests - James C. Stegen; Nathan G. Swenson; Renato Valencia; Brian J. Enquist; Jill Thompson (Global Ecology and Biogeography, 2009)
Aim It is increasingly accepted that the mean wood density of trees within a forest is tightly coupled to above‐ground forest biomass. It is unknown, however, if a positive relationship between forest biomass and mean community wood density is a general phenomenon across forests. Understanding spatial variation in biomass as a function of wood density both within and among forests is important for predicting changes in stored carbon in response to global change, and here we evaluated the generality of a positive biomass–wood density relationship within and among six tropical forests. Location Costa Rica, Panama, Puerto Rico and Ecuador. Methods Individual stem data, including diameter at breast height and spatial position, for six forest dynamics plots were merged with an extensive wood density database. Individual stem biomass values were calculated from these data using published statistical models. Total above ground biomass, total basal area and mean community wood density were also quantified across a range of subcommunity plot sizes within each forest. Results Among forests, biomass did not vary with mean community wood density. The relationship between subcommunity biomass and mean wood density within a forest varied from negative to null to positive depending on the size of subcommunities and forest identity. The direction of correlation was determined by the associated total basal area–mean wood density correlation, the slope of which increased strongly with whole forest mean wood density. Main conclusions There is no general relationship between forest biomass and wood density, and in some forests, stored carbon is highest where wood density is lowest. Our results suggest that declining wood density, due to global change, will result in decreased or increased stored carbon in forests with high or low mean wood density, respectively.

Opposing assembly mechanisms in a Neotropical dry forest: implications for phylogenetic and functional community ecology - Nathan G. Swenson; Brian J. Enquist (Ecology, 2009)
Species diversity is promoted and maintained by ecological and evolutionary processes operating on species attributes through space and time. The degree to which variability in species function regulates distribution and promotes coexistence of species has been debated. Previous work has attempted to quantify the relative importance of species function by using phylogenetic relatedness as a proxy for functional similarity. The key assumption of this approach is that function is phylogenetically conserved. If this assumption is supported, then the phylogenetic dispersion in a community should mirror the functional dispersion. Here we quantify functional trait dispersion along several key axes of tree life‐history variation and on multiple spatial scales in a Neotropical dry‐forest community. We next compare these results to previously reported patterns of phylogenetic dispersion in this same forest. We find that, at small spatial scales, coexisting species are typically more functionally clustered than expected, but traits related to adult and regeneration niches are overdispersed. This outcome was repeated when the analyses were stratified by size class. Some of the trait dispersion results stand in contrast to the previously reported phylogenetic dispersion results. In order to address this inconsistency we examined the strength of phylogenetic signal in traits at different depths in the phylogeny. We argue that: (1) while phylogenetic relatedness may be a good general multivariate proxy for ecological similarity, it may have a reduced capacity to depict the functional mechanisms behind species coexistence when coexisting species simultaneously converge and diverge in function; and (2) the previously used metric of phylogenetic signal provided erroneous inferences about trait dispersion when married with patterns of phylogenetic dispersion.

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Improved abundance prediction from presence–absence data - Erin Conlisk; John Conlisk; Brian Enquist; Jill Thompson; John Harte (Global Ecology and Biogeography, 2009)
Aim Many ecological surveys record only the presence or absence of species in the cells of a rectangular grid. Ecologists have investigated methods for using these data to predict the total abundance of a species from the number of grid cells in which the species is present. Our aim is to improve such predictions by taking account of the spatial pattern of occupied cells, in addition to the number of occupied cells. Innovation We extend existing prediction models to include a spatial clustering variable. The extended models can be viewed as combining two macroecological regularities, the abundance–occupancy regularity and a spatial clustering regularity. The models are estimated using data from five tropical forest censuses, including three Panamanian censuses (4, 6 and 50 ha), one Costa Rican census (16 ha) and one Puerto Rican census (16 ha). A serpentine grassland census (8 × 8 m) from northern California is also studied. Main conclusions Taking account of the spatial clustering of occupied cells improves abundance prediction from presence–absence data, reducing the mean square error of log‐predictions by roughly 54% relative to a benchmark Poisson predictor and by roughly 34% relative to current prediction methods. The results have high statistical significance.

Species abundance distributions: moving beyond single prediction theories to integration within an ecological framework - Brian J. McGill; Rampal S. Etienne; John S. Gray; David Alonso; Marti J. Anderson; Habtamu Kassa Benecha; Maria Dornelas; Brian J. Enquist; Jessica L. Green; Fangliang He; Allen H. Hurlbert; Anne E. Magurran; et al. (Ecology Letters, 2007)
Species abundance distributions (SADs) follow one of ecology’s oldest and most universal laws – every community shows a hollow curve or hyperbolic shape on a histogram with many rare species and just a few common species. Here, we review theoretical, empirical and statistical developments in the study of SADs. Several key points emerge. (i) Literally dozens of models have been proposed to explain the hollow curve. Unfortunately, very few models are ever rejected, primarily because few theories make any predictions beyond the hollow‐curve SAD itself. (ii) Interesting work has been performed both empirically and theoretically, which goes beyond the hollow‐curve prediction to provide a rich variety of information about how SADs behave. These include the study of SADs along environmental gradients and theories that integrate SADs with other biodiversity patterns. Central to this body of work is an effort to move beyond treating the SAD in isolation and to integrate the SAD into its ecological context to enable making many predictions. (iii) Moving forward will entail understanding how sampling and scale affect SADs and developing statistical tools for describing and comparing SADs. We are optimistic that SADs can provide significant insights into basic and applied ecological science.

Latitudinal patterns of range size and species richness of New World woody plants - Michael D. Weiser; Brian J. Enquist; Brad Boyle; Timothy J. Killeen; Peter M. Jørgensen; Gustavo Fonseca; Michael D. Jennings; Andrew J. Kerkhoff; Thomas E. Lacher Jr; Abel Monteagudo; M. Percy Núñez Vargas; Oliver L. Phillips; et al. (Global Ecology and Biogeography, 2007)
Aim Relationships between range size and species richness are contentious, yet they are key to testing the various hypotheses that attempt to explain latitudinal diversity gradients. Our goal is to utilize the largest data set yet compiled for New World woody plant biogeography to describe and assess these relationships between species richness and range size. Location North and South America. Methods We estimated the latitudinal extent of 12,980 species of woody plants (trees, shrubs, lianas). From these estimates we quantified latitudinal patterns of species richness and range size. We compared our observations with expectations derived from two null models. Results Peak richness and the smallest‐ and largest‐ranged species are generally found close to the equator. In contrast to prominent diversity hypotheses: (1) mean latitudinal extent of tropical species is greater than expected; (2) latitudinal extent appears to be decoupled from species richness across New World latitudes, with abrupt transitions across subtropical latitudes; and (3) mean latitudinal extents show equatorial and north temperate peaks and subtropical minima. Our results suggest that patterns of range size and richness appear to be influenced by three broadly overlapping biotic domains (biotic provinces) for New World woody plants. Main conclusions Hypotheses that assume a direct relationship between range size and species richness may explain richness patterns within these domains, but cannot explain gradients in richness across the New World.

Adaptive differences in plant physiology and ecosystem paradoxes: insights from metabolic scaling theory - BRIAN J. ENQUIST; ANDREW J. KERKHOFF; TRAVIS E. HUXMAN; EVAN P. ECONOMO (Global Change Biology, 2007)
The link between variation in species‐specific plant traits, larger scale patterns of productivity, and other ecosystem processes is an important focus for global change research. Understanding such linkages requires synthesis of evolutionary, biogeograpahic, and biogeochemical approaches to ecological research. Recent observations reveal several apparently paradoxical patterns across ecosystems. When compared with warmer low latitudes, ecosystems from cold northerly latitudes are described by (1) a greater temperature normalized instantaneous flux of CO 2 and energy; and (2) similar annual values of gross primary production (GPP), and possibly net primary production. Recently, several authors attributed constancy in GPP to historical and abiotic factors. Here, we show that metabolic scaling theory can be used to provide an alternative ‘biotically driven’ hypothesis. The model provides a baseline for understanding how potentially adaptive variation in plant size and traits associated with metabolism and biomass production in differing biomes can influence whole‐ecosystem processes. The implication is that one cannot extrapolate leaf/lab/forest level functional responses to the globe without considering evolutionary and geographic variation in traits associated with metabolism. We test one key implication of this model – that directional and adaptive changes in metabolic and stoichiometric traits of autotrophs may mediate patterns of plant growth across broad temperature gradients. In support of our model, on average, mass‐corrected whole‐plant growth rates are not related to differences in growing season temperature or latitude. Further, we show how these changes in autotrophic physiology and nutrient content across gradients may have important implications for understanding: (i) the origin of paradoxical ecosystem behavior; (ii) the potential efficiency of whole‐ecosystem carbon dynamics as measured by the quotient of system capacities for respiration, R , and assimilation, A ; and (iii) the origin of several ‘ecosystem constants’– attributes of ecological systems that apparently do not vary with temperature (and thus with latitude). Together, these results highlight the potential critical importance of community ecology and functional evolutionary/physiological ecology for understanding the role of the biosphere within the integrated earth system.

Ecosystem allometry: the scaling of nutrient stocks and primary productivity across plant communities - Andrew J. Kerkhoff; Brian J. Enquist (Ecology Letters, 2006)
A principal challenge in ecology is to integrate physiological function (e.g. photosynthesis) across a collection of individuals (e.g. plants of different species) to understand the functioning of the entire ensemble (e.g. primary productivity). The control that organism size exerts over physiological and ecological function suggests that allometry could be a powerful tool for scaling ecological processes across levels of organization. Here we use individual plant allometries to predict how nutrient content and productivity scale with total plant biomass (phytomass) in whole plant communities. As predicted by our model, net primary productivity as well as whole community nitrogen and phosphorus content all scale allometrically with phytomass across diverse plant communities, from tropical forest to arctic tundra. Importantly, productivity data deviate quantitatively from the theoretically derived prediction, and nutrient productivity (production per unit nutrient) of terrestrial plant communities decreases systematically with increasing total phytomass. These results are consistent with the existence of pronounced competitive size hierarchies. The previously undocumented generality of these ‘ecosystem allometries’ and their basis in the structure and function of individual plants will likely provide a useful quantitative framework for research linking plant traits to ecosystem processes.

Plant allometry, stoichiometry and the temperature‐dependence of primary productivity - Andrew J. Kerkhoff; Brian J. Enquist; James J. Elser; William F. Fagan (Global Ecology and Biogeography, 2005)
Aim While physical constraints influence terrestrial primary productivity, the extent to which geographical variation in productivity is influenced by physiological adaptations and changes in vegetation structure is unclear. Further, quantifying the effect of variability in species traits on ecosystems remains a critical research challenge. Here, we take a macroecological approach and ask if variation in the stoichiometric traits (C: N: P ratios) of plants and primary productivity across global‐scale temperature gradients is consistent with a scaling model that integrates recent insights from the theories of metabolic scaling and ecological stoichiometry. Location This study is global in scope, encompassing a wide variety of terrestrial plant communities. Methods We first develop a scaling model that incorporates potentially adaptive variation in leaf and whole‐plant nutrient content, kinetic aspects of photosynthesis and plant respiration, and the allometry of biomass partitioning and allocation. We then examine extensive data sets concerning the stoichiometry and productivity of diverse plant communities in light of the model. Results Across diverse ecosystems, both foliar stoichiometry (N : P) and ‘nitrogen productivity’ (which depends on both community size structure and plant nutrient content) vary systematically across global scale temperature gradients. Primary productivity shows no relationship to temperature. Main conclusions The model predicts that the observed patterns of variation in plant stoichiometry and nutrient productivity may offset the temperature dependence of primary production expected from the kinetics of photosynthesis alone. Our approach provides a quantitative framework for treating potentially adaptive functional variation across communities as a continuum and may thus inform studies of global change. More generally, our approach represents one of the first explicit combinations of ecological stoichiometry and metabolic scaling theories in the analysis of macroecological patterns.

Allometric growth, life‐history invariants and population energetics - Evan P. Economo; Andrew J. Kerkhoff; Brian J. Enquist (Ecology Letters, 2005)
Population and community level processes must be at least partially determined by variation in the body sizes of constituent individuals, implying quantitative scaling relations can be extended to account for variation in those processes. Here we integrate allometric growth and life‐history invariant theories, and use this approach to develop theory describing the energetics of stationary populations. Our predictions approximate, with no free parameters, the scaling of production/biomass and assimilation/biomass ratios in mammalian populations and work partially for fish populations. This approach appears to be a promising direction and suggests the need for further development of the growth and life‐history models, and extensions of those theories.

Thermodynamic and metabolic effects on the scaling of production and population energy use - S. K. Morgan Ernest; Brian J. Enquist; James H. Brown; Eric L. Charnov; James F. Gillooly; Van M. Savage; Ethan P. White; Felisa A. Smith; Elizabeth A. Hadly; John P. Haskell; S. Kathleen Lyons; Brian A. Maurer; et al. (Ecology Letters, 2003)
Ecosystem properties result in part from the characteristics of individual organisms. How these individual traits scale to impact ecosystem‐level processes is currently unclear. Because metabolism is a fundamental process underlying many individual‐ and population‐level variables, it provides a mechanism for linking individual characteristics with large‐scale processes. Here we use metabolism and ecosystem thermodynamics to scale from physiology to individual biomass production and population‐level energy use. Temperature‐corrected rates of individual‐level biomass production show the same body‐size dependence across a wide range of aerobic eukaryotes, from unicellular organisms to mammals and vascular plants. Population‐level energy use for both mammals and plants are strongly influenced by both metabolism and thermodynamic constraints on energy exchange between trophic levels. Our results show that because metabolism is a fundamental trait of organisms, it not only provides a link between individual‐ and ecosystem‐level processes, but can also highlight other important factors constraining ecological structure and dynamics.

Allometric scaling of maximum population density: a common rule for marine phytoplankton and terrestrial plants - Andrea Belgrano; Andrew P. Allen; Brian J. Enquist; James F. Gillooly (Ecology Letters, 2002)
A primary goal of macroecology is to identify principles that apply across varied ecosystems and taxonomic groups. Here we show that the allometric relationship observed between maximum abundance and body size for terrestrial plants can be extended to predict maximum population densities of marine phytoplankton. These results imply that the abundance of primary producers is similarly constrained in terrestrial and marine systems by rates of energy supply as dictated by a common allometric scaling law. They also highlight the existence of general mechanisms linking rates of individual metabolism to emergent properties of ecosystems.